How BPS-Statistics Indonesia to Handle The Effectiveness of Information System of Public Budgeting Management? - Kurniawan, Wawan; Sanapiah, A. Aziz (Jurnal Ilmiah Administrasi Publik, 2021)
The BPS-Statistics Indonesia tried to take a step to realize good governance, especially in conducting good budget management by implementing an information system of public budgeting management known as the BackOffice Information System. The purpose of this study is to find out how the effectiveness of the implementation of the BackOffice Information System at BPS. This study uses a qualitative method by conducting case studies in BPS Headquarter (Jakarta). Conducting online interview to 59 operators and users, as well as conducting deep interview to 10 key informants. The result shows that the implementation of the BackOffice Information System is effective and practical because this information system is accurate and timely in presenting data and budget information, integrated with several other information systems. Users and key informants also are satisfied with the performance of this information system. The implementation of Back Office also contributes to increasing the realization of the budget and the achievement of BPS performance and to maintaining the Financial Statements performance: Unqualified Opinion (from BPK-the Audit Board of the Republic of Indonesia).